Contemporary Turkey in conflict ethnicity, Islam and politics - Abbas, Tahir (Edinburgh University Press, 2017)
Placing the period within its historical and contemporary context, Tahir Abbas argues that what it is to be ethnically, religiously and culturally Turkish has been transformed. These conflicts are defining the future of the nation.